ANALYSIS OF THE INFLUENCE OF GREEN FINANCE, GOOD CORPORATE GOVERNANCE, AND FINANCIAL PERFORMANCE ON COMPANY VALUE IN THE BANKING INDUSTRY IN INDONESIA - Imami, Nurul; Laras Asih, Dessy Novitasari (Journal of Accounting and Financial Issue (JAFIS), 2024)
This research is motivated by the fact that activities carried out by humans unconsciously have many negative effects on nature, one of which is climate change, which is already uncertain. This research analyzes the influence of green finance, good corporate governance, and financial performance on company value. This research uses quantitative research methods. Data collection techniques were obtained from sources related to banking companies in the form of annual reports and sustainability reports for 2020–2022 published by banking companies on the official website of the Indonesia Stock Exchange (IDX) and the official websites of related banking companies. The data analysis technique used in this research uses panel data regression analysis, and the test tool uses EViews13. The results of this research show that: (1) Green Finance has no effect on Company Value; (2) Good Corporate Governance has no influence on Company Value; (3) Financial Performance influences Company Value; and (4) Green Finance, Good Corporate Governance, and Financial Performance simultaneously influence Company Value.